Identification of the fragment containing cross-reacting antigenic determinants of the variable surface glycoprotein of Trypanosoma brucei - Barbet, A.F.; Musoke, A.J.; Shapiro, S.Z.; Mpimbaza, G.W.N.; McGuire, T.C. (Cambridge University Press, 1981)
125I-labelled, isolated variable surface glycoproteins (VSGs) ofTrypanosoma b. bruceibind both homologous and heterologous anti-VSG sera and binding to heterologous antisera may be blocked by other unlabelled VSGs (Barbet & McGuire, 1978). This paper presents results which suggest that oligosaccharide residues have importance in the antigenic structure of VSG cross-reacting determinants. The ability of VSG to bind heterologous anti-VSG sera was destroyed by periodate oxidation but not by extensive proteolysis. A VSG glycopeptide fragment was isolated from two different VSGs, which blocked by 100 % the binding of VSG to heterologous anti-VSG sera and therefore contained the cross-reacting determinants. The native glycopeptide fragment was resistant to digestion with trypsin, pronase or leucine aminopeptidase and prolidase. We also show that a VSG synthesized in the reticulocyte lysate cell-free system was not immunoprecipitated by heterologous anti-VSG sera in contrast to the same VSG labelled by metabolic incorporation of [35S]methioninein vivo.